Isolation and subjective welfare: evidence from South Asia. - Fafchamps, M; Shilpi, F (University of Chicago Press, 2009)
Using detailed geographical and household survey data from Nepal, this article investigates the relationship between isolation and subjective welfare. This is achieved by examining how distance to markets and proximity to large urban centers are associated with responses to questions about income and consumption adequacy. Results show that isolation is associated with a significant reduction in subjective assessments of income and consumption adequacy, even after controlling for consumption expenditures and other factors. The reduction in subjective welfare associated with isolation is much larger for households that are already relatively close to markets. These findings suggest that welfare assessments based on monetary income and consumption may seriously underestimate the subjective welfare cost of isolation, and hence will tend to bias downward the assessment of benefits to isolation-reducing investments such as roads and communication infrastructure.